With chocolate against hate speech : exploring corporate activism - Ketola, Katja (2021)
Companies of today have their roles to play in advancing positive change in society. This societal contribution has also slowly become the decisive point of difference for consumers who are expecting companies to speak out on critical socio-political issues and participate in solving those alongside traditional changemakers. (e.g. Bhagwat et al. 2020.) This phenomenon, termed corporate activism, confronts companies with fundamental challenges on how to run a business and communicate on its behalf. This qualitative study aims to gain more insight on this prominent, yet, still scarcely researched phenomenon by focusing on a single case: Fazer, a major Finnish FMCG company, and its activist effort on hate speech from 2018. The study sheds light on how corporate activism is perceived from both the corporate and public perspectives, and on the factors that should be taken into consideration when engaging in corporate activism. The research data consists of a semi-structured interview and publications collected from Fazer’s owned media, owned and earned social media, as well as from news media. The data was analysed with an abductive approach, using content analysis. The findings suggest that Fazer engages in corporate activism primarily due to the company’s inherent sense of duty although activism has benefitted the company also financially and reputationally. Fazer’s fight against hate speech was received with mixed emotions and met with an active counter-mobilization; the public did not seem to understand Fazer’s motivation to address hate speech nor the relevance of the issue. Besides, the public discussion mostly circulated around the phenomenon of corporate activism rather than focusing on the issue at the heart of the campaign. The findings support the notion raised in prior research (e.g. Weinzimmer & Esken 2016) that considering how a stand is taken instead of merely focusing on what the stand is may help companies design ever more purposeful and successful efforts. This study also further underlines the importance of communication, and stresses candid collaboration and co-creation.